2020
DOI: 10.1111/hsc.13107
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal influences on self‐management in the eHealth era: Predicting the uses of eHealth tools for self‐care in America

Abstract: Drawing on the social cognitive theory and the comprehensive model of information seeking, this study proposes a theoretical framework that systematically examines the role of interpersonal factors in individuals' self‐management in the eHealth context. The framework was tested with a sample of 965 eHealth users drawn from the National Cancer Institute's 2018 Health Information National Trends Survey. Structural equation modelling was performed to model the relationships among patient‐centred communication, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
(104 reference statements)
1
11
0
Order By: Relevance
“…The population-based group had fewer treatments and, therefore, fewer problems coping with their symptoms compared with the OCC group [ 41 , 42 ]. The OCC group had more reasons to investigate what could possibly help them, in which case eHealth tools for self-care are an accessible option [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population-based group had fewer treatments and, therefore, fewer problems coping with their symptoms compared with the OCC group [ 41 , 42 ]. The OCC group had more reasons to investigate what could possibly help them, in which case eHealth tools for self-care are an accessible option [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…They probably expect that they can improve their health through active participation and self-management. Indeed, the characteristics of the survivors in the OCC group are factors that influence the self-management of individuals in an eHealth environment [ 43 ]. Could this OCC group represent the starting point for user uptake and implementation of web-based interventions, many of which remain on the shelf [ 46 , 47 ]?…”
Section: Discussionmentioning
confidence: 99%
“…Thus, "reminders, " "persuasion, " and "encouragement" against tobacco use likely benefit rural patients' self-management of chronic illness. However, it should be noted that the same population is constrained by limited health literacy and poor access to healthcare resources (e.g., primary care providers, specialist doctors, and online healthcare information) (14,50,51). Thus, middle-aged and older rural patients may not fully benefit from their social networks when it comes to medication use behavior (19,52).…”
Section: Discussionmentioning
confidence: 99%
“…As both Bourdieu and Veenstra in their work on social capital theory note that rich healthcare resources only mean an increasing chances and opportunities to access resources (7,8); the maximum utilization of healthcare resources is closely related to the individuals' ability to maintain long-term social connections and participation in social real-life activities (9)(10)(11), which is social engagement. This because that effective self-management demands social interaction and collaboration between patients and their environment so they may successfully manage the difficulties that arise from having a chronic illness (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ’s meta-analysis of 44 studies on OHIS found that trust of information source, as well as quality and usefulness of information rather than perceived risk and self-efficacy were more important factors that affect individual’s OHIS behavior ( Wang et al , 2021 ). With the advancement of information and communication technologies, patients are expected to take an active role and responsibility for their health, increasing the need for information-related self-management ( Introne and Goggins, 2019 ; Sun and Jiang, 2020 ; Yang and Wu, 2020 ). In China, the outbreak of severe acute respiratory syndrome (SARS) in 2003 marked the emergence of OHIS ( Cao et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%